Measuring exposure to organochlorinated pesticides - Silva Mendonça Gulnar Azevedo e (Cadernos de Saúde Pública, 1998)
Environmental epidemiological investigations in cancer remain, with rare exceptions, inconclusive. The difficulties of establishing patterns of measurements of exposure in the human body is one of the limitations of these studies. The findings of six recent epidemiological studies that analyzed the association between organochlorinated compounds and breast cancer are reviewed in considering the problems of measuring environmental exposure through biological markers. The epidemiological evidence based on these studies do not indicate a risk of breast cancer related to organochlorines. Some aspects that may partially explain this absence of risk are discussed regarding the investigation of environmental carcinogenic agents in populations with low but homogeneously sprayed levels of exposure.